STRATEGI KOPING ANAK TERAKHIR DALAM MENGATASI KEHILANGAN AYAH DAN KESEPIAN: SEBUAH PENDEKATAN KUALITATIF: LAST CHILD STRATEGY IN OVERCOMING FEELINGS OF LONELINESS AND LOSS OF FATHER IN A FAMILY ENVIRONMENT THAT IS NOT INTACT - Ramdani, Reviandy Azhar; Rojabi, Muhammad Nafis; Mubarok, Moch Chusni; Roihan, Roihan; Fuadi, Difa Azman Refah; Kholis, Nur (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
This study aims to investigate the strategies utilized by last-born children to cope with feelings of loneliness and the loss of a father within a broken family structure. Employing a qualitative approach, data were collected through auto-biography and deep interview ten of the last-born children from families experiencing broken homes. Data analysis was conducted to identify themes and patterns of strategies emerging from the interviews. The findings of the study indicate that last-born children adopt various strategies to cope with feelings of loneliness and the loss of a father. Key strategies include seeking support from other family members, cultivating close relationships with peers, and engaging in activities that provide a sense of achievement. Some children also utilize social media as a channel for emotional expression and seeking support. The research findings emphasize the importance of providing specific support to last-born children in broken families experiencing the loss of a father. Effective strategies to assist last-born children in overcoming emotional challenges include providing regular access to professional counseling to discuss feelings of loneliness and loss. Additionally, empowering last-born children to build strong social networks through interactions with peers, family, or support groups is crucial. Involving last-born children in expressive activities, such as art or sports, can also aid them in expressing emotions and diverting attention from sadness. Teaching last-born children emotional management and life skills can help them feel more resilient and confident in facing difficult situations. Intervention programs involving support groups or life skills classes can provide the necessary guidance to address these emotional difficulties. Consistent support from other family members is also important to ensure that last-born children feel safe and supported in their environment. Keywords: Broken Home,Loneliness, Family Support, Fatherless, Peers. Abstrak Penelitian ini bertujuan untuk menyelidiki strategi yang digunakan oleh anak terakhir untuk mengatasi perasaan kesepian dan kehilangan ayah dalam keluarga yang tidak utuh. Dengan menggunakan pendekatan kualitatif berdasarkan auto biografi dan wawancara terhadap 10 anak terakhir dari keluarga yang mengalami broken home. Analisis data dilakukan untuk mengidentifikasi tema dan pola strategi yang muncul dari wawancara. Hasil penelitian menunjukkan bahwa anak terakhir mengadopsi berbagai strategi untuk mengatasi perasaan kesepian dan kehilangan ayah. Strategi utama meliputi mencari dukungan dari anggota keluarga lainnya, membangun hubungan dekat dengan teman sebaya, dan mengejar kegiatan yang memberikan rasa pencapaian. Beberapa anak juga menggunakan media sosial sebagai saluran untuk ekspresi emosi dan pencarian dukungan. Temuan penelitian ini menekankan pentingnya memberikan dukungan khusus bagi anak terakhir dalam keluarga yang mengalami broken home dan kehilangan ayah. Strategi yang efektif untuk membantu anak terakhir mengatasi tantangan emosional termasuk menyediakan akses rutin ke konseling profesional untuk mendiskusikan perasaan kesepian dan kehilangan. Selain itu, anak terakhir dapat diberdayakan untuk membangun jaringan sosial yang kuat melalui interaksi dengan teman sebaya, keluarga, atau kelompok dukungan. Melibatkan anak terakhir dalam aktivitas ekspresif, seperti seni atau olahraga, juga dapat membantu mereka mengekspresikan perasaan dan mengalihkan perhatian dari kesedihan. Mengajarkan keterampilan manajemen emosi dan hidup kepada anak terakhir dapat membantu mereka merasa lebih tangguh dan percaya diri dalam menghadapi situasi sulit. Program intervensi yang melibatkan kelompok dukungan atau kelas keterampilan hidup dapat memberikan panduan yang diperlukan untuk mengatasi kesulitan emosional ini. Dukungan yang konsisten dari anggota keluarga lainnya juga penting untuk memastikan anak terakhir merasa aman dan didukung dalam lingkungannya. Kata Kunci: Keluarga Tidak Utuh, Kesepian, Dukungan Keluarga, Ketiadaan Ayah, Teman Sebaya